Taking Stock, December 2016 : An Update on Vietnam's Recent Economic Developments - World Bank (World Bank, Hanoi, 2016)
Over recent decades, Vietnam’s agricultural sector has made enormous progress, realizing major gains in productivity and output and contributing to national goals related to food security, poverty reduction, social stability, and trade. Nevertheless, there are growing concerns related to the quality and sustainability of Vietnam’s agricultural growth and related patterns of development. A comparatively low quality of growth is manifested by low smallholder farmer profitability, considerable under-employment among agricultural workers, mixed or uncertain product quality and food safety, low value addition, and limited technological or institutionalinnovation. Some agricultural growth has come at the expense of the environment in the forms of deforestation, biodiversity loss, land degradation, water pollution, and greenhouse gas emissions. In most locations, agricultural growth has involved an increase in cropping areas or intensities and ever higher uses of inputs and natural resources. Hence, more output has come from more and more inputs and increasing environmental costs. Vietnamese agriculture now sits at a turning point. The sector now faces growing domestic competition—from cities, industry, and services—for labor, land and water. Rising labor costs are beginning to inhibit the sector’s ability to compete internationally as a low cost producer of bulk undifferentiated commodities. The country’s ruralyouth have rising aspirations for living standards. Vietnam’s expanding consumer class and trade partners are expecting higher standards, both for products and production practices. Going forward, Vietnam’s agriculture will need to generate ‘more from less’. That is, it will need to generate more economic value—and farmer and consumer welfare—using less natural and human resources and without degrading the environment. It will need to rebrand itself and increasingly compete on the bases of innovation, reliable supply, predictable quality, and assured food safety and environmental protection.